pH对醇法花生蛋白功能特性的影响 及其在馒头中的应用Effect of pH on the functional properties of peanut protein prepared by alcohol leaching and their application in steamed bun - 赵树超1，张相风2，王文昕1，郭兴凤2，逄飞1 ZHAO Shuchao1, ZHANG Xiangfeng2, WANG Wenxin1, GUO Xingfeng2, PANG Fei1 (Zhongguo youzhi, 2025)
旨在为醇法花生蛋白的应用提供参考，以低温压榨花生饼经索氏抽提脱脂后的花生粕（CP）为原料，采用醇法制备花生蛋白产品（D1和D2），系统研究了pH对花生蛋白功能特性的影响。另外，将花生蛋白添加至面粉中制作馒头，分析了馒头的理化指标，以考察花生蛋白对馒头品质的影响。结果表明：与CP相比，D1和D2的溶解性下降，但持水性、持油性、乳化特性、起泡特性以及胶凝性均提高；在pH 5～9范围内，随pH增大，D1的溶解性、起泡性、乳化性和胶凝性先增后减，持水性降低，持油性增加，D2的溶解性、持油性增加，持水性、起泡性、胶凝性整体呈降低趋势，乳化性先增后减；D1和D2的添加量（1%～3%）对馒头比容、水分含量、pH、孔隙结构参数（孔隙率、孔隙密度和孔隙平均面积）基本无显著影响，对表皮色泽影响显著，D1和D2的添加促使馒头更柔软和有弹性，其中添加1%D1的馒头综合评分为91.07分，显著高于纯面粉馒头的（85.88分）。综上，醇法加工可有效提升花生蛋白除溶解性外的其他功能特性，适量添加于面粉中可提升馒头综合品质。 In order to provide reference for the application of alcohol-leached peanut protein, defatted peanut meal (CP) obtained from cold-pressed peanut cake after Soxhlet extraction was taken as the raw material to prepare peanut protein products(D1 and D2) by alcohol leaching, and the effects of pH on the functional properties of the products were studied. In addition, the products were added to flour to prepare steamed bun, and the physicochemical indexes of steamed bun were analyzed to investigate the influence of peanut protein on its quality. The results showed that the solubility of D1 and D2 decreased, while their water-holding capacity, oil-holding capacity, emulsifying property, foaming property, and gelation property all improved compared with CP. Within the pH range of 5 to 9, as the pH increased, the solubility, foaming capacity, emulsifying capacity and gelation property of D1 all first increased and then decreased, the water-holding capacity decreased, the oil-holding capacity increased. The solubility and oil-holding capacity of D2 increased, while the water-holding capacity, foaming capacity and gelation property generally showed a decreasing trend, and the emulsifying capacity first increased and then decreased. The addition of D1 and D2 (1%-3%) had no significant effect on the specific volume, moisture content, pH and pore structure parameters (porosity, pore density, and average pore area) of steamed bun, but significantly affected the surface color. The addition of D1 and D2 made the steamed bun softer and more elastic. Among them, the comprehensive score of steamed bun with 1% D1 added was 91.07, which was significantly higher than that of pure flour steamed bun (8588). In conclusion, alcohol leaching process can effectively enhance the functional properties of peanut protein except for solubility, and appropriate addition to flour can improve the overall quality of steamed bun.